ADEN ECO-TOURISM: REALITY AND OBSTACLES - Mahfood, Ibtehal (Finance and Business Economies Review, 2019)
This research aims to shed light on the reality of eco-tourism in Aden and on glitches that restrict its improvement. In order to achieve objectives of the research, descriptive method was employed to describe reality (research subject-matter). The researcher concluded a number of results including the fact that Aden has many factors, both natural and human, that enable it to host eco-tourism, but this is prevented by various obstacles. Based on the research conclusions, recommendations were presented to contribute to developing and reviving eco-tourism if considered seriously. The most important such recommendations are: providing financial resources, drawing development plans, policies and programs, working on attracting national and international investments in this field while taking into account all ecological considerations and support for infrastructure, protecting and developing all aspects of the city’s natural and historical heritage.